Persepsi Guru terhadap Implementasi Kurikulum Merdeka di Madrasah - Badrus Sholeh, Muhammad; Kamsan, Nur; Aliyah, Himmatul (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
This study investigates teachers' perceptions of the Merdeka Curriculum. The qualitative design of this study was conducted on class VII teachers at MTs Negeri 3 Demak. The study's data was gathered through interviews, observations, and field notes. This study focuses on teachers' perceptions on the plan, implementation, and assessment of Merdeka Curriculum learning. The study's findings show that (1) teachers' perceptions of learning planning are adequate. (2) teachers' perceptions of learning implementation are not very positive because most teachers are still not optimal in implementing the learning process as required by the Independent Curriculum; and (3) teachers' perceptions of learning evaluation are good. Teachers recognize the significance of assessment in the Merdeka Curriculum. Teachers have employed a range of evaluation techniques, including observations, performance assessments, written tests, oral exams, and portfolios. Based on these findings, teachers should conduct a thorough analysis of the Merdeka Curriculum's implementation. Teachers must think openly when adopting the Independent Curriculum to ensure future adjustments and improvements.